Synthesis of globin RNA in enucleated differentiating murine erythroleukemia cells (The Rockefeller University Press, 1987)
In an earlier report (Volloch, V., 1986, Proc. Natl. Acad. Sci. USA., 83:1208-1212) we had presented evidence for the occurrence of the cytoplasmic synthesis of globin mRNA and of RNA complementary to globin mRNA which differed from DNA-dependent transcription by its insensitivity to actinomycin D. In this paper, we describe the use of enucleated differentiating mouse erythroleukemia cells to demonstrate directly the occurrence of cytoplasmic synthesis of both positive- and negative-strand globin RNA. For this purpose, we developed an enucleation procedure which yielded pure cytoplasts from differentiated mouse erythroleukemia cells in the absence of cytochalasin B and selectively permeabilized the cytoplasts to small molecules by treatment with dextran sulfate and saponin. The permeabilized cytoplasts incorporated [3H]dUTP into positive- and negative-strand globin RNA and experiments with mercurated nucleotide substrate suggested that this process involved de novo RNA synthesis rather than limited terminal nucleotide addition. Globin RNA synthesis required Mg++, was inhibited by Mn++, and was unaffected by the addition of Zn++. Studies of its response to inhibitors of DNA-dependent RNA synthesis showed that it differed from that process in its insensitivity to actinomycin D and alpha-amanitin, but that like many other macromolecular biosynthetic reactions it was inhibited by rifamycin AF/ABDP and aurintricarboxylic acid. These observations provide additional evidence for the occurrence of cytoplasmic RNA- dependent RNA synthesis in differentiated cells and show permeabilized enucleated cells to be a useful experimental system for further studies of the characteristics of that process.